Human papillomavirus (HPV) vaccine uptake among a community-recruited sample of gay, bisexual, and other men who have sex with men in the three largest cities in Canada from 2017 to 2019. Issue 28 (23rd June 2021) - Grewal, R.; Deeks, S.L.; Hart, T.A.; Cox, J.; De Pokomandy, A.; Grennan, T.; Lambert, G.; Moore, D.; Brisson, M.; Coutlée, F.; Gaspar, M.; George, C.; et al.
Abstract: Introduction: In 2015/2016, Canada's largest provinces implemented publicly-funded human papillomavirus (HPV) vaccination programs for gay, bisexual, and other men who have sex with men (GBM) ≤ 26 years old. We sought to describe HPV vaccine uptake among GBM and determine barriers and facilitators to vaccine initiation with a focus on healthcare access and utilization. Methods: Engage is a cohort study among GBM aged 16 + years in three Canadian cities recruited from 2017 to 2019 via respondent driven sampling (RDS). Men completed a comprehensive questionnaire at baseline. By publicly-funded vaccine eligibility (≤26 years old = eligible for vaccination, ≥27 years old = ineligible), we described HPV vaccine uptake (initiation = 1 + dose, completion = 3 doses) and explored factors associated with vaccine initiation using Poisson regression. All analyses were weighted with the RDS-II Volz-Heckathorn estimator. Results: Across the three cities, 26–35% and 14–21% of men ≤ 26 years and 7–26% and 2–9% of men ≥ 27 years initiated and completed HPV vaccination, respectively. Vaccine initiation was significantly associated with STI/HIV testing or visiting a HIV care specialist in the past six months (≤26: prevalence ratio[PR] = 2.15, 95% confidence interval[CI] 1.06–4.36; ≥27: PR = 2.73, 95%CI 1.14–6.51) and past hepatitis A or B vaccination (≤26: PR = 2.88, 95%CI 1.64–5.05; ≥27: PR = 2.03, 95%CI 1.07–3.86). Among men ≥ 27 years old, vaccine initiation was also positively associated with accessing PrEP, living in Vancouver or Toronto, but negatively associated with identifying as Latin American and increasing age. Vaccine initiation was twice as likely among men ≥ 27 years with private insurance versus no insurance. Conclusions: Sixty-five to 74% of men eligible for publicly-funded vaccine across the three cities remained unvaccinated against HPV by 2019. High vaccine cost may partly explain even lower uptake among men ≥ 27 years old. Men seeking sexual health care were more likely to initiate vaccination; bundling vaccination with these services may help improve HPV vaccine uptake.